Causas del desarrollo y mecánica del crecimiento (2004)
The theme of this essay is one of the most important addressed by economists, at least since Adam Smith, and one that will always attract attention. And in our case, that of economists who have witnessed a country and a time whose rates of increase in GDP per capita have gone in about two or three decades, from relatively normal to others rather low average levels, the attraction of this issue has become especially intense. Overcame so intense that, in my case, to the consciousness of the immense difficulties they would face if addressed, and knowing that the chance of saying something really new was nil, or almost.